MODEL PENGEMBANGAN KARAKTER ENTREPRENEURSHIP SANTRI MELALUI UNIT USAHA KOPONTREN DI PONDOK PESANTREN AL-HIKAM BURNEH BANGKALAN - Ely Inriani; Taufiqur Rahman (PROCEEDING UMSURABAYA, 2022)
This article discusses the importance of developing the entrepreneurial character of students through the kopontren business unit (cooperative boarding school), which has a function to directly and significantly determine the development of entrepreneurial character through business units as a form of facilities provided by Islamic boarding schools as a form for developing the entrepreneurial nature of students who are must be set, there are many development models that are applied in the Islamic boarding school, one of which is the Bazaar, the Bazaar itself has a very large impact on the development of the entrepreneurial character of students in the Islamic boarding school so by doing this research I hope to be able to get a significant picture related to the model of entrepreneurship character development through the Kapontren business unit at the Al-Hikam Islamic Boarding School so that the entrepreneurial character development model through this business unit can be an alternative for developing entrepreneurial character For students, this study uses a qualitative approach where data collection techniques use documentation, observation and thorough interviews with several students at the Al-Hikam Islamic Boarding School and the administrators or coordinators who hold the Kopontren business unit at the boarding school. Meanwhile, for data analysis, the descriptive qualitative analysis serves to analyze or describe the situation from various data collected in interviews or direct observations that occur in the field.Keywords: entrepreneurship; development style; Islamic boarding school